Hyperplasias of supra renal cortex in horses - Santos, Jefferson Andrade dos; Pires, Amaury Romeiro; Silva Junior, José Fernandes da (Pesquisa Agropecuaria Brasileira, 2014)
Of 149.394 horses slaughtered in Brazil for consumption, there were 32 cases of suprarenal hyperplasia (0,02%). In four cases, the process was clearly nodular, and in 28 cases the lesions were difuse. In the nodular forms, the nodosities were found in the poles of the gland, reaching the size of a chicken egg. In the difuse forms, the gland showed a uniform hypertrophy and its parenchyma exhibited different aspects. Microscopically examined, there was a predominance of a simple hyperplasia process; in certain cases, the hyperplasia culminated in the liberation of cholesterol crystals and their calcification; in a few cases only, the gland exhibited different signs of necrosis. The hyperplasic cells were rich in fats, reaching a scummy aspect, somewhat similar to an adipose cell. Those fats were sudanophilic. The process studied is probably correlated with castration, since most of the examined animals were in this condition. But it is also possible that those hyperplasias were induced by stress, this caused by intense muscular strain, since the examined material was from work and saddle horses.